2023
DOI: 10.1101/2023.07.10.548392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unreviewed science in the news: The evolution of preprint media coverage from 2014-2021

Alice Fleerackers,
Kenneth Shores,
Natascha Chtena
et al.

Abstract: It has been argued that preprint coverage during the COVID-19 pandemic constituted a paradigm shift in journalism norms and practices. This study examines whether, in what ways, and to what extent this is the case using a sample of 11,538 preprints posted on four preprint servers---bioRxiv, medRxiv, arXiv, and SSRN---that received coverage in 94 English-language media outlets between 2014--2021. We compared mentions of these preprints with mentions of a comparison sample of 397,446 peer reviewed research artic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(2021a) found that journalists in the Asia/Pacific region were among the most likely to use preprints, whereas those in African and Middle Eastern countries were among the least likely. In addition, Fleerackers et al (2023) found little or no change in the coverage of non-COVID-19 preprints during the pandemic period, suggesting that journalists’ embrace of COVID-19 preprints may not extend to preprints on other topics, nor those posted during less urgent crisis contexts.…”
Section: Journalists’ Use Of Open Access Publications and Preprints D...mentioning
confidence: 93%
See 1 more Smart Citation
“…(2021a) found that journalists in the Asia/Pacific region were among the most likely to use preprints, whereas those in African and Middle Eastern countries were among the least likely. In addition, Fleerackers et al (2023) found little or no change in the coverage of non-COVID-19 preprints during the pandemic period, suggesting that journalists’ embrace of COVID-19 preprints may not extend to preprints on other topics, nor those posted during less urgent crisis contexts.…”
Section: Journalists’ Use Of Open Access Publications and Preprints D...mentioning
confidence: 93%
“…Similarly, coverage of preprints in German news outlets was relatively low before the pandemic, but surged in 2020 and 2021 ( Simons & Schniedermann, 2023 ). Finally, a study found that preprints were featured in less than 2% of media coverage of research before the pandemic, but that this proportion surged to almost 4% after the onset of COVID-19 ( Fleerackers et al , 2023 ). Moreover, this surge appeared to be driven entirely by COVID-19 preprints, as the launch of the medical preprint server medRxiv in 2019 had little or no effect on rates of preprint coverage.…”
Section: Journalists’ Use Of Open Access Publications and Preprints D...mentioning
confidence: 99%
“…During the COVID-19 pandemic, there has been both a proliferation of scientific data, and a major shift in how results were disseminated, with many researchers opting to post their work as preprints ahead of or instead of publication in scientific journals. 1 5 Preprints are scientific manuscripts that are posted on freely accessible preprint servers (such as medRxiv, bioRxiv, PsyArXiv, MetaArXiv or arXiv) which have not gone through formal peer review. They take between 24 and 48 hours to become ‘live’ – after basic checks by server administrators, ensuring the content of the manuscript is scientific text within the scope of the server, and not spam or plagiarised.…”
Section: Introductionmentioning
confidence: 99%